PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE SMARTFREN (STUDI PADA KONSUMEN SMARTFREN DI KOTA SEMARANG) - Panggayuh Arya Bagaskara, 13.05.51.0242 (Students Journal of Economic and Management, 2017)
The purpose of this research is to examine and analyze the effect of product quality, price perception, and promotion on purchasing decision of smartphone product to consumers in Semarang City.Sampling method using purposive sampling with limit of product usage period more or less for one year and at least 17 years old. The influence between variables is explained by using multiple regression analysis method. Based on the results of statistical tests in this study can be concluded that product quality significantly influence the purchase price perception decision significant effect on purchasing decisions, as well as significant promotion of the decision to purchase smartfren smartphone products on Smartfren consumers in the city of Semarang. Keywords: Product Quality, Price Perception, Promotion, and Purchase Decision